Mass spectrometry-based metabolomics for the elucidation of alkaloid biosynthesis and function in invasive Vincetoxicum rossicum populations - Christine J. Kempthorne; Max St. Pierre; Andrew Le; Stuart Livingstone; James McNulty; Marc W. Cadotte; David K. Liscombe (Phytochemistry, 2024)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Are urban systems beneficial, detrimental, or indifferent for biological invasion? - Marc W. Cadotte; Simone Louise E. Yasui; Stuart Livingstone; J. Scott MacIvor (Biological Invasions, 2017)

Explaining ecosystem multifunction with evolutionary models - Marc W. Cadotte; Stuart W. Livingstone; Simone‐Louise E. Yasui; Russell Dinnage; Jin‐tian Li; Robin Marushia; James Santangelo; Wensheng Shu (Ecology, 2017)
Ecosystem function is the outcome of species interactions, traits, and niche overlap – all of which are influenced by evolution. However, it is not well understood how the tempo and mode of niche evolution can influence ecosystem function. In evolutionary models where either species differences accumulate through random drift in a single trait or species differences accumulate through divergent selection among close relatives, we should expect that ecosystem function is strongly related to diversity. However, when strong selection causes species to converge on specific niches or when novel traits that directly affect function evolve in some clades but not others, the relationship between diversity and ecosystem function might not be very strong. We test these ideas using a field experiment that established plant mixtures with differing phylogenetic diversities and we measured ten different community functions. We show that some functions were strongly predicted by species richness and mean pairwise phylogenetic distance ( MPD , a measure of phylogenetic diversity), including biomass production and the reduction of herbivore and pathogen damage in polyculture, while other functions had weaker (litter production and structural complexity) or nonsignificant relationships (e.g., flower production and arthropod abundance) with MPD and richness. However, these divergent results can be explained by different models of niche evolution. These results show that diversity‐ecosystem function relationships are the product of evolution, but that the nature of how evolution influences ecosystem function is complex.